Comparing the effects of aerobic and stretching exercises on the intensity of primary dysmenorrhea in the students of universities of bushehr. - Farideh Vaziri; Azam Hoseini; Farahnaz Kamali; Khadijeh Abdali; Mohamadjavad Hadianfard; Mehrab Sayadi (Tehran University of Medical Sciences, 2015)
Objective:To compare the effects of aerobic and stretching exercises on severity of primary dysmenorrhea. Materials and methods:This randomized clinical trial was conducted on 105 female students who were suffering from primary dysmenorrhea. The participants were divided into aerobic exercise, stretching exercise, and control groups. The two intervention groups did the exercises three times a week for eight weeks (two menstrual cycles). The intensity of dysmenorrhea was determined using a modified questionnaire that assessed several symptoms of dysmenorrhea. After all, the data were compared between and within groups through analysis of variance. Results:Before the intervention, the mean intensity of dysmenorrhea was 40.38 ± 5.5, 37.40 ± 3.8, and 38.45±3.3 in aerobic, stretching, and control groups, respectively, but the difference was not statistically significant. After the intervention, however, a significant difference was found among the three groups regarding the mean intensity of dysmenorrhea in the first and second menstrual cycles. Also, a significant difference was observed between the aerobic group and the control group as well as between the stretching group and the control group. Within group comparisons showed a significant difference in the aerobic and the stretching group before and after the interventions. However, no such difference was observed in control group. Conclusion:Both aerobic and stretching exercises were effective in reducing the severity of dysmenorrhea. Therefore, women could choose one of these two methods with regard to their interest and lifestyle.